2007
DOI: 10.1111/j.1600-6143.2007.01821.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Ehrlichiosis in Transplant Recipients

Abstract: To characterize the impact of immunosuppression on human ehrlichiosis, we reviewed cases of ehrlichiosis occurring in transplant recipients and immunocompetent patients at three hospitals in Nashville, Tennessee. Between 1998 and 2006, 15 transplant patients were identified as having ehrlichiosis, diagnosed either by whole blood polymerase chain reaction (PCR) (n = 14) or serology (n = 1). They were compared with 43 immunocompetent patients diagnosed by whole blood PCR. We retrospectively collected demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 26 publications
4
56
2
Order By: Relevance
“…12,13 Risk factors for severe or fatal outcome include immune compromise and older age: several accounts of ehrlichiosis and anaplasmosis among prior organ allograft recipients have been reported. [31][32][33][34][35][36] In the current surveillance report, 9 patients reported by CRF had a history of organ transplant, and 239 reported other conditions associated with immune compromise, including cancer, diabetes, and arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Risk factors for severe or fatal outcome include immune compromise and older age: several accounts of ehrlichiosis and anaplasmosis among prior organ allograft recipients have been reported. [31][32][33][34][35][36] In the current surveillance report, 9 patients reported by CRF had a history of organ transplant, and 239 reported other conditions associated with immune compromise, including cancer, diabetes, and arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Persons who have compromised immune systems as a result of immunosuppressive therapies, human immunodeficiency virus (HIV) infection (145,146), organ transplantation (147,148), or splenectomy more frequently have severe symptoms of ehrlichiosis and are hospitalized more often (13). Case-fatality rates among persons who are immunosuppressed are higher than those among the general population, on the basis of U.S. passive surveillance and some case series (5,13,145); delays in recognition and initiation of appropriate antibacterial treatment in this population might contribute to increased mortality (149). Although older age (≥60 years) and immunosuppression are risk factors for severe ehrlichiosis (5,10,13), many cases of severe or fatal ehrlichiosis have been described in previously healthy children and young adults (128).…”
Section: Clinical Coursementioning
confidence: 99%
“…Fewer severe manifestations have been reported with E. ewingii than with E. chaffeensis ehrlichiosis (145), and no deaths have been described. Although E. ewingii infection has been considered more common in persons who are immunosuppressed (149), recent passive surveillance data indicated that most (74%) reported cases were not in persons with documented immunosuppression (5). Similar to E. chaffeensis ehrlichiosis, patients with E. ewingii ehrlichiosis commonly have leukopenia, thrombocytopenia, and elevated hepatic transaminase levels.…”
Section: Ehrlichia Ewingii Ehrlichiosismentioning
confidence: 99%
“…6,10 Patients with ehrlichiosis and who are immunocompromised, especially from human immunodeficiency virus (HIV), cancer treatments, or organ transplants, are at highest risk for severe outcome. 8,[15][16][17][18][19][20][21][22][23] As recommended by the American Academy of Pediatrics (AAP) and the Centers for Disease Control and Prevention (CDC), doxycycline, a tetracycline-class antibiotic, is the treatment of choice for children and adults of all ages with rickettsial disease, including ehrlichiosis; treatment should never be withheld pending laboratory confirmation. 9,13,24 Treatment with doxycycline within the first 5 days of illness has been shown to decrease severity of disease in patients when compared with patients who were treated later in the course of illness.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Human ehrlichiosis caused by E. ewingii is less commonly reported and most infections have historically occurred among immunocompromised patients. 2,[6][7][8][9] Symptoms of ehrlichiosis are nonspecific and typically begin within 7-14 days of exposure. 6 Patients are most likely to seek medical attention approximately 3 days after onset of symptoms.…”
Section: Introductionmentioning
confidence: 99%